2020
DOI: 10.1186/s40900-020-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-oriented research competencies in health (PORCH) for researchers, patients, healthcare providers, and decision-makers: results of a scoping review

Abstract: Background The Canadian Institutes of Health Research funded a program, "patient-oriented research" (POR), to change the way health research is done. POR involves patients and their families/caregivers as equal partners on research teams with researchers, healthcare providers and decision-makers. The authors of this paper work through a unit in British Columbia, Canada that functions to help research teams learn how to do patient-oriented research. We felt that we could not train people if we didn't first unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
(143 reference statements)
0
48
0
1
Order By: Relevance
“…Boote et al identified eight principles of “successful” consumer involvement in research, two of which included training and support of consumers and researchers [ 21 ]. Likewise, Frisch et al identified research knowledge and skills as core competencies for researchers and patients involved in patient-oriented research [ 22 ]. Petit-Zeman has argued that professionals and patients involved in research require training and support “ perhaps most crucially to help them understand each others’ worlds [ 23 ].” Of note, while ‘scientific jargon’ has been identified by patients as a barrier to patient engagement, other patients have suggested that training – in the context of randomized trials – may lead to the ‘professionalization’ of patient partners [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boote et al identified eight principles of “successful” consumer involvement in research, two of which included training and support of consumers and researchers [ 21 ]. Likewise, Frisch et al identified research knowledge and skills as core competencies for researchers and patients involved in patient-oriented research [ 22 ]. Petit-Zeman has argued that professionals and patients involved in research require training and support “ perhaps most crucially to help them understand each others’ worlds [ 23 ].” Of note, while ‘scientific jargon’ has been identified by patients as a barrier to patient engagement, other patients have suggested that training – in the context of randomized trials – may lead to the ‘professionalization’ of patient partners [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Establishing partnerships with patients and patient groups (PGs) to engage them in all levels of clinical trials (CTs), including in real-world evidence research, is increasingly explored and applied globally [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Keys to such engagement—also referred to as co-design research, participatory research, patient-oriented research (POR), patient-involved research, patient public involvement, patient participation, co-creative research, citizen science, patient-centric initiative, open science—are the understanding and the manifestation of the concept of patient centricity or patient centeredness [ 1 , 3 , 4 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite developments on patient and PG engagement in health research, including the well-known frameworks of Patient-Centered Outcomes Research Institute (PCORI) in the US, INVOLVE in the UK, and Strategy for Patient-Oriented Research (SPOR) in Canada [ 3 , 4 , 6 , 23 , 38 , 39 , 40 ], in practice the prevalence of patient engagement across CTs remains extremely low; less than 1% as reported by Fergusson et al [ 15 ] in a systematic review from May 2011 to June 2016. An unmet need resides in providing tangible tools for CT stakeholders to commit to the principle of patient centricity and patient engagement [ 5 , 41 , 42 ] as well as empowering patients to fulfil their role specifically in cancer CTs.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Others describe the training and competencies of researchers required for effective stakeholder engagement. 16,17 A review of stakeholder engagement highlighted that the evidence of impact was weak due to inconsistent data and lack of detail. 3 Studies to date emphasize the importance of evaluating the process of involving patients and the public in all phases of research and the need for evidence of how stakeholders' perspectives can be https://doi.org/10.1017/cts.2020.552 Downloaded from https://www.cambridge.org/core.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several journal articles describe frameworks for how to integrate patient and family advisors in all phases of the research process and include specifics of how to share decision-making between researchers and other stakeholders [14][15][16]. Others describe the training and competencies of researchers required for effective stakeholder engagement [16,17]. A review of stakeholder engagement highlighted that the evidence of impact was weak due to inconsistent data and lack of detail [3].…”
Section: Introductionmentioning
confidence: 99%